Kryzys w Unii Europejskiej. Propozycje nowych pól i pytań badawczych - Czachór, Zbigniew (Rocznik Integracji Europejskiej, 2015)
Researchers have posed questions concerning the dynamics and crisis of European integration since its beginnings. They have proposed and continue to propose new research fields and questions on the theoretical and empirical approaches to the issue of irregularities in the Euro- pean Union, in particular the most recent ones. The author of this paper joins this trend, and takes a standpoint with respect to the (dependent and independent) variables that define the distorted dynamics of EU integration which have been analytically determined. The author intends to expose the distorted dynamics of the EU system and European integration, as well as the crises that accompany them, fuelling numerous academic, political and media debates and polemics. The research agenda of both an epistemological and empirical nature concerns the academic search for an anti-crisis finalité politique. The paper confirms the pluralistic nature of integration ideology, where no single theory or theoretical concept suffices to explain the increasingly complex, multi-directional crisis-related phenomena and interactions following from European integration. Therefore “the Union as described and academically analysed” is not always equivalent to “the Union in action.” That is why we are dealing with the growing detachment of theoretical concepts from the practical activities within the process of European integration. This paper demonstrates that the theoretical attempts at presenting European integration and its crises result in a certain permeation of paradigms between different concepts and in spontaneous promulgation and ‘merging’ of selected elements of theoretical outlooks that were assigned to quite different, or even contradictory theories and concepts.